THROUGH BRAND IMAGE, PRICE PERCEPTION, AND WORD OF MOUTH) ON THE DECISION TO PURCHASE SYIFA POTATO DONUTS - Rizki Ayunda Lestari; Anastasya Putri Khumaira.S; Rakhmawati Purba; Willy Cahyadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of Brand Image, Price Perception, and Word of Mouth (WOM) on purchasing decisions of Syifa Potato Donuts in Tebing Tinggi, North Sumatra, amidst tight culinary competition. Using a quantitative approach with SmartPLS analysis on 96 consumer respondents through a Likert scale questionnaire, the results show that partially the three variables have no significant effect (t-statistic <1.96), but simultaneously have a positive and significant effect (F-count 10.2469> F-table 3.09) with a contribution of 51.5% (R-square 0.515). The conclusion emphasizes an integrated strategy of the three factors to build competitive advantage.